Social Environment and Agonistic Interactions: Strategies in a Small Social Mammal - Andino, Natalia del Pilar (2011)
In group-living species, the development of agonistic interactions among conspecifics may be affected by socio-ecological factors, such as size and composition of social group, and availability of nests and food. We analysed the importance of size and composition of social groups on agonistic interactions among males in the Southern mountain cavy (Microcavia australis). We made behavioural observations in four social groups of different size and composition. We recorded two types of agonistic interactions: agonistic displays and direct agonistic behaviours; both types increased in the breeding season. A social group composed of a high number of males was associated with high frequency of agonistic displays. Direct agonistic behaviours were also influenced by the interaction of season and number of males per social group and number of females per social group. Agonistic interactions were also recorded among males of different socials groups in the breeding season. Agonistic displays were most frequent among males of the same social group, whereas direct agonistic behaviours were most common among males of different social groups. These results suggest that social factors affect agonistic interactions among males of Southern mountain cavy and that in a conflict situation, males develop different strategies, such as increased frequency of agonistic behaviours in breeding season and intragroup cooperation for defence of oestrous females.